زراعة الأعضاء وأثرها في حفظ النفس "زراعة القلب أنموذجًا" (Comprehensive Journal of Science, 2026)
This study examines organ transplantation and its impact on the preservation of human life as one of the contemporary medical issues closely related to the higher objectives of Islamic law, particularly the objective of preserving life, which is considered one of the five essential necessities (al-ḍarūriyyāt al-khams). Islamic law has established rulings that aim to achieve human welfare and prevent harm across all times and places.The study adopts a set of integrated methodologies. The deductive method is employed as the primary approach to analyze relevant Islamic legal texts and derive rulings therefrom. The inductive method is used to survey and trace the opinions of jurists concerning organ transplantation and brain death. The descriptive method is applied to present scholarly views, analyze contested evidence, and identify the legal basis for applying rulings to contemporary cases, while the comparative method is utilized to compare juristic opinions regarding brain death, organ transplantation, and related medical issues.The study concludes with several significant findings. It establishes that, in Islamic law, death is defined as the separation of the soul from the body, and that brain death or brainstem death alone is insufficient to constitute legal death unless accompanied by the cessation of all vital bodily functions. It further concludes that organ transplantation from a brain-dead individual constitutes an act of causing death and cannot be analogized to legal death; therefore, such transplantation is not permissible. Moreover, the study affirms the permissibility of organ donation from a living person to another, provided that it does not result in significant harm or bodily disfigurement to the donor.The study also addresses the transplantation of animal organs into humans, noting that this issue remains complex and surrounded by ambiguity. Nevertheless, it concludes that the use of pig organs is permissible in cases of necessity, according to the stronger juristic opinion, as the prohibition pertains to the consumption of pork rather than the utilization of its organs. Additionally, the study highlights that medical advancement and proven therapeutic success may elevate the ruling of medical treatment from permissibility or recommendation to obligation in certain circumstances, when preserving life is highly probable.The study ultimately underscores the flexibility of Islamic law and its capacity to address contemporary medical developments within the framework of its higher objectives and legal principles, thereby ensuring the preservation of human life while balancing benefits and harms.